The therapeutic potential of exercise to treat cachexia - Lira, Fábio Santos de [UNESP]; Antunes, Barbara de M. M. [UNESP]; Seelaender, Marília; Neto, José C. Rosa (Wolters Kluwer Health, 2015)
To discuss the role of physical exercise in the attenuation of cancer cachexia-associated symptoms, and upon the outcome of chemotherapy, with special focus on the anti-inflammatory role of chronic exercise. The review addresses the recent findings regarding the positive effects of endurance and strength exercise training upon metabolic dysfunction, systemic inflammation and body composition alterations in the syndrome of cachexia. The employment of different exercise protocol strategies, in respect to intensity, duration, work load and in concomitance with pharmacological treatment is considered. Cachexia is a multifactorial wasting syndrome afflicting patients with cancer, chronic obstructive pulmonary disease, chronic heart failure, trauma, among other diseases. This condition markedly compromises the quality of life, treatment outcome and survival. Recent literature indicates an unequivocal role of chronic exercise in modulating cachexia and other cancer-associated dysfunctions. Exercise is proposed as a complementary treatment in cancer, and represents a function-preserving, anti-inflammatory and metabolism-modulating strategy with low cost, and high versatility and availability. Furthermore, exercise decreases cancer recurrence and presents a positive impact on public health management, reducing hospitalization and medication costs.